The Morphological characteristics of Porang (Amorphophallus muelleri Blume) in Timor-Leste and their correlation with the climatic conditions: Amorphophallus muelleri Blume in Timor-Leste - de Deus da Cruz, Nice; Azrianingsih , Rodiyati; Ribeiro da Costa, Hermenegildo (Journal of Tropical Life Science, 2024)
Porang (Amorphophallus muelleri Blume) is native to the forests of Timor-Leste, with cultivation starting in 2017. This study examined the morphological characteristics and nutrient content of porang from six gardens across Timor-Leste, assessing relationships with climatic factors. Various morphological traits and climate variables, including elevation, were measured. Nutrient analysis of porang tubers utilized chromatographic and mass spectrometric techniques, while principal component analysis helped identify links between morphology, nutrient content, and abiotic factors. Despite some qualitative similarities, such as colour and leaf patterns, significant differences were noted in measurable traits. Findings indicated that environmental conditions significantly influenced porang growth. For instance, higher air humidity in the Bobonaro District positively affected plant height and canopy width. In contrast, elevated temperatures and soil conductivity in the Liquiça District influenced leaf venation. The Aileu District exhibited the highest bulbil abundance, while larger tubers were found in the Ermera District, which is at a higher elevation. The Manufahi District had rich organic carbon content, and porang in Manatuto, with higher soil pH, produced more bulbils. However, drought conditions in Manatuto led to moisture loss and partial tuber decay. The highest glucomannan concentration was found in tubers from Bobonaro (10.25%), followed by Liquiça (9.87%) and Ermera (9.81%). Overall, environmental factors like elevation, soil temperature, and humidity significantly impacted porang characteristics and yield.